Nasal Septal Flaps for Repair of Large or Recurrent Palatal Fistula: Report of Technique and 4-Year Experience. Issue 3 (22nd November 2022) - Fox, Carly M.; McKenzie, Jo-Lyn C.; Morris, Helen C.; Phua, Yun S.; Bade, Stuart A.; Bowman, James; Theile, Richard J.
Abstract : Summary: Large or multiply recurrent oronasal fistulas following cleft palate repair present a challenging problem. Nasal septal mucoperichondrial flaps have been widely used for repair of skull base defects; however, their use in the repair of oronasal cleft palate fistulas has not previously been described. In this pilot study, the authors describe anterior palatal fistula repair using a nasal septal flap and review their experience with this technique over 4 years. Fourteen patients with anterior palatal fistulas not amenable to repair using local palatal flaps were included for analysis. The mean size of the fistula was 12 mm in maximum dimension. Flap healing with complete or near-complete closure of fistula was achieved in 13 patients (93%). Five of these patients had a small, slit-like residual fistula that was asymptomatic. Nasal septal flaps are a new technique for repair of large or recurrent palatal fistulas. The procedure is well-tolerated with minimal side effects, high success rate, and low incidence of recurrence. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV.